Education and training adaptations for health workers during the COVID-19 pandemic: a scoping review of lessons learned and innovations - Boutros, Perla; Kassem, Nour; Nieder, Jessica; Jaramillo, Catalina; von Petersdorff, Jakob; Walsh, Fiona J.; Bärnighausen, Till; Barteit, Sandra (Healthcare, 2023)
Introduction: The COVID-19 pandemic has considerably impacted the clinical education and training of health workers globally, causing severe disruptions to learning environments in healthcare facilities and limiting the acquisition of new clinical skills. Consequently, urgent adaptation measures, including simulation training and e-learning, have been implemented to mitigate the adverse effects of clinical education. This scoping review aims to assess the impact of COVID-19 on medical education and training, examine the implemented adaptation measures, and evaluate their effectiveness in improving health workers’ education and training during the pandemic. Methods: Employing the PRISMA-ScR framework and Arksey and O’Malley’s methodological guidance, we conducted a scoping review, systematically searching PubMed, medRxiv, Google, and DuckDuckGo databases to account for the grey literature. The search included studies published between 1 December 2019 and 13 October 2021, yielding 10,323 results. Of these, 88 studies focused on health worker education and training during the pandemic. Results: Our review incorporated 31,268 participants, including physicians, medical trainees, nurses, paramedics, students, and health educators. Most studies (71/88, 81%) were conducted in high-income and lower-middle-income countries. The pandemic’s effects on health workers’ clinical skills and abilities have necessitated training period extensions in some cases. We identified several positive outcomes from the implementation of simulation training and e-learning as adaptation strategies, such as enhanced technical and clinical performance, increased confidence and comfort, and an expanded global educational outreach. Conclusions: Despite challenges like insufficient practical experience, limited interpersonal interaction opportunities, and internet connectivity issues, simulation training, e-learning, and virtual training have proven effective in improving clinical education and training during the COVID-19 pandemic. Further research is required to bolster preparedness for future pandemics or similar situations.
Gesehen am 10.05.2024